James Louis Robertson papers - Robertson, James Louis, 1907-1994.; Robertson, Andrew J., 1845-1918.; Robertson, James Louis, 1907-1994.
Correspondence, diaries, speeches, writings, subject files, genealogical material, newspaper clippings, and other papers relating primarily to Robertson's service as a member of the Board of Governors of the Federal Reserve System. Includes material pertaining to the U.S. Federal Banking Commission and the U.S. Federal Open Market Committee; diaries (1869-1901) kept by Robertson's father, Andrew J. Robertson; and a draft of Robertson's book, What Generation Gap??? A Dialogue on America (1970).
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Chief clerk of the U.S. Senate Post Office, special agent of the U.S. Federal Bureau of Investigation, reserve naval officer, deputy comptroller of the currency, and member of the Board of Governors of the Federal Reserve System.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Robertson family; United States. -- Federal Banking Commission; United States. -- Federal Open Market Committee; Board of Governors of the Federal Reserve System (U.S.); Monetary policy -- United States; United States -- Economic policy -- 20th century; FBI agents; Naval officers; Public officials